Os inconfidentes nas Minas Gerais: uma relação entre a Geografia e a Literatura Setecentista de Cláudio Manuel da Costa, Tomás Antônio Gonzaga e Alvarenga Peixoto - Araújo, Kárita de Fátima (2014)
Order to understand the way in which it sued the construction of national identity and the Brazilian territorial formation in the context of the eighteenth-century Minas Gerais, we ve tried doing it in the light of the literary works of poets conspiracy. So, we chose Villa Rica from Claudio Manuel da Costa; Cartas chilenas from Tomas Antonio Gonzaga and Canto Genetlíaco from Inácio José de Alvarenga Peixoto. Working in the intersection between geography and literature, we seek to combine the artistic expressions of the agents who actually participated in the Minas Conspiracy to storms that formed the society of the eighteenth century mining and spatial components. In this sense, the poetry of the conspiracy was essential to analyze the condition of the mining captaincy just as it was presented. Some elements have been invaluable in assisting us in this analysis, such as understanding the concept of sertão for that locale and period as well as their occupation and isolation condition, the development and decay of the gold cycle and the relationships established between Minas Gerais and the captaincies of São Paulo and Rio de Janeiro in order to subsequently compose together a single independent nation of Portugal . Understand also the colonial relations between Brazil and Portugal was vital to assess the reasons that the mining elite to unite around a movement that, fortified by dissatisfaction with the Portuguese managed under the colony, had the intention of transforming the Minas Gerais and perhaps São Paulo and Rio de Janeiro, in an independent territory. In addition to the political and economic issues that motivated the movement die conspirator, there were still those of an ideological character, which were essential to characterize the motions involved. This time, we turn our gaze to the acquired inspiration from Enlightenment ideological current that valued clarity and rationality and that was widely studied and used by poets conspiracy. Coupled with the Enlightenment was also the Arcadian literary current that enabled the conspirators poets express their ideas. Therefore, we tried to consider all those aspects involving expressive subjects ( GOLDMANN, 1979 ) around the same ideal in order to reveal not only the worldview ( GOLDMANN, 1979) reflected in literary works, but also the reality of Minas Gerais of the eighteenth-century, expressed in literary texts.